The Effect of Work Discipline and Training on Employee Performance with Work Experience as an Intervening Variable in Class D Hospitals in Pasaman - Nurkhofifah; Putra, Ramdani Bayu; Yosi Puspita Sari; Hasmaynelis Fitri (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research aims to analyze the determinants of employee performance and work experience using work discipline and employee training at Passaman Class D Hospital as independent variables. The population and sample of this study amounted to 72 respondents with the sampling technique using the total sampling method. The methodology used is Structural Equation Modeling (SEM) using the SmartPLS tool. The findings show that work discipline has a positive impact on work experience. It also shows that training has a significant positive impact on professional experience. Work discipline also has a significant positive influence on employee performance. Training is proven to have a positive impact on employee performance. Work experience has been proven to have a positive impact on employee performance. Work discipline is proven to have a positive influence on work experience through employee performance. Training has a positive impact on work experience through employee performance